4 Pages

# Derivatives

Course Number: MATH 6, Fall 2009

College/University: University of Illinois,...

Word Count: 549

Rating:

###### Document Preview

Math 234 Practice Problems: Calculate Derivatives 1. Calculate d (f (x)) dx (also known as f (x)) of these functions a. f (x) = 3 b. f (x) = x2 c. f (x) = x + 1 d. f (x) = 2x3 + 5x2 4x 1 e. f (x) = 10x4 3x3 + 2x2 5x + 10 f. f (x) = x 2 g. f (x) = x h. f (x) = 3 x i. f (x) = 5 4 x + 4x2 j. f (x) = x1 k. f (x) = l. f (x) = 1 x 1 x2 2 x 1 m. f (x) = 5x3 2x + 55 n. f (x) = x o. f (x) = 3x p. f (x) = x3 q....

##### Unformatted Document Excerpt
Coursehero >> Illinois >> University of Illinois, Urbana Champaign >> MATH 6

Course Hero has millions of student submitted documents similar to the one
below including study guides, practice problems, reference materials, practice exams, textbook help and tutor support.

Course Hero has millions of student submitted documents similar to the one below including study guides, practice problems, reference materials, practice exams, textbook help and tutor support.

234 Math Practice Problems: Calculate Derivatives 1. Calculate d (f (x)) dx (also known as f (x)) of these functions a. f (x) = 3 b. f (x) = x2 c. f (x) = x + 1 d. f (x) = 2x3 + 5x2 4x 1 e. f (x) = 10x4 3x3 + 2x2 5x + 10 f. f (x) = x 2 g. f (x) = x h. f (x) = 3 x i. f (x) = 5 4 x + 4x2 j. f (x) = x1 k. f (x) = l. f (x) = 1 x 1 x2 2 x 1 m. f (x) = 5x3 2x + 55 n. f (x) = x o. f (x) = 3x p. f (x) = x3 q. f (x) = 4x3 + 3 x4 r. f (x) = x4 Note that we have a pattern here, where given any constant d d c R, dx (cf (x)) = c dx (f (x)). You should make use of this fact to simplify future calculations - it can be the dierence from blindly using product or quotient rule and simply applying the power rule for some! 1 2 s. f (x) = x(x + 1) t. f (x) = 2x(x + 1) u. f (x) = (x + 1)(x 1) v. f (x) = (x + 2)(x + 5) w. f (x) = 3(x 3)(x 4) x. f (x) = 4(x2 + 10x)(x 15) y. f (x) = (x + 1)(x + 2)(x + 3) z. f (x) = (x 4)(x 5)(x 6) . f (x) = x2 (x + 2) . f (x) = x3 (x 1) . f (x) = x(2x 1) . f (x) = 2x2 (3x2 + 2x + 1) . f (x) = (4x3 + 3x2 + 2x + 1)(x2 x 1) . f (x) = (x4 + x3 + x2 + x + 1)2 (x 1)2 . f (x) = (x + 1)3 (x 1)3 . f (x) = (2x 1)(3x + 1)3 (10x 1)2 . f (x) = (x2 + 1)2 (2x3 + x2 1)3 (3x4 + + 3x2 2x + 1)4 . f (x) = . f (x) = . f (x) = . f (x) = . f (x) = x+1 x x x2 2 (x+1)2 (x1)3 (x3 +3x1) (5x2 +x+1)2 (3x2 +1)2 (2x+1) x2 . f (x) = 3 3 +x x 3 2 +9 x . f (x) = . f (x) = ( x2x )2 (10x2 + 10 + 1)3 1 x . f (x) = ( x+1 + x3 )4 (4x3 2x2 4) 2 . f (x) = x (x x+1 + 2) . f (x) = (4x2 + 1) x1 4x . f (x) = 5x2 + 3x . f (x) = . f (x) = 5 10x1 x2 +2 (3x1)(5x5 3x)2 r 2 10x2 3 + 3x 3 2 x 3x 1 * (5x+1)4 * denotes a challenge problem that tests your knowledge on usage of all of the rules . f (x) = ex . f (x) = ex 3 +x . f (x) = ex + ex . f (x) = (ex + 1)(ex 1) . f (x) = e3x (2x + 1)2 . f (x) = . f (x) = . f (x) = e5x +1 10x3 (3x+2)3 e5x3 2 2 2 2 e3x 5 +x . f (x) = (e6x . f (x) = ln x )2 . f (x) = ln(10x + 1) 1. f (x) = ln(14x5 + 3x) 4 2. f (x) = ln ex 3. f (x) = ln e5x 4. f (x) = (ln(x2 + 1) + 1)(ln(x) + 1) 5. f (x) = (ln(3x 1))2 (6x2 + 1)2 6. f (x) = 7. f (x) = 8. f (x) = ln 5x 4x ln(x2 1) ln(x2 +2x+1) ln(x3 1) 1 9. f (x) = (ln(x2 + 3x)) 3 10. f (x) = e( ln x) 11. f (x) = eln(x 2 +1) 12. f (x) = (ln(ex ) 1)(eln(x ) + 1) 13. f (x) = ex 3 +x2 2 2 ln(2x + 1) ln(4x + 3) + x2 (3x + 4) 14. f (x) = e3x 15. f (x) = 4 +4x3 6x+1 x1 e2x+3 ln(x2 1) 16. (ex + ex ) ln(4x2 1)